Diplopia Following Short Treatment for Moderate Amblyopia. (3rd July 2017) - Hoole, Janice; Barrow, Natasha
ABSTRACT: A case of an autistic child, aged 8 years, who reported binocular diplopia following just 2 hours total occlusion per day for 6 weeks for strabismic/anisometropic amblyopia is reported. There was a history of known long-standing reduced uniocular acuity without treatment. Pretreatment Sbisa bar assessment suggested moderate suppression. The diplopia was treated over 6 months including occluding the amblyopic eye and gradually reducing the density of the occluder until fixation with the nonamblyopic eye could be maintained and diplopia ignored. Possible contributing factors are discussed.